A training programme to facilitate parents' orientation to and definition of problems experienced in parenting young children with moderate to severe communication disabilities - Uys, C.J.E. (Catharina Jacoba Elizabeth) (University of Pretoria, 2016)
Thesis (DPhil)--University of Pretoria, 2015.